Collaborative research in theory and practice the poetics of letting go - Pahl, Kate 1962-; Steadman-Jones, Richard; Vasudevan, Lalitha (Bristol University Press, 2022)
This book invites the reader to think about collaborative research differently. Using the concepts of 'letting go' and 'poetics', it envisions collaborative research as a space where relationships are forged with the use of arts-based and multimodal ways of seeing, inquiring, and representing ideas.